ANALISIS KEUNTUNGAN USAHA JAMUR TIRAM (Pleurotus sp) PADA BELLA FARM DI DESA MOKUPA KECAMATAN TOMBARIRI KABUPATEN MINAHASA - Cynthia Meylin Lahama; Paulus Adrian Pangemanan; Ribka Magdalena Kumaat (AGRI-SOSIOEKONOMI, 2019)
The objective of this research is to analyze the profit received by Bella Farm in one production of Oyster Mushrooms for three months. The research was conducted in December 2018 to February 2019, starting from preparation to preparing the report. The data used are primary. Primary data was obtained from direct interviews with oyster mushroom business owner Bella Farm. While secondary data was obtained from the North Sulawesi Agriculture and Animal Husbandry Service, the internet through Google in the form of journal articles and theses related to this research. Data collected in this study are presented in table form and then described and analyzed using profit analysis. Profits are obtained from the difference between revenue and costs incurred. The results ofthe research showed that Bella Farm in Mokupa Village, Tombariri Sub-district, Minahasa Regency received a profit of Rp. 24.714.705 per one-time production process for three months at a cost of Rp.22.185.295 and the value of R / C cost revenue is 2.11, which means that Bella Farm has a profit.*jnkd+eprm*